Vitamin D3–elicited CD14+ human skin dendritic cells promote thymic stromal lymphopoietin–independent type 2 T‐helper responses. Issue 7 (27th January 2021) - Brulefert, Adrien; Hoste, Astrid; Muller, Quentin; Fauny, Jean‐Daniel; Mueller, Christopher G.; Flacher, Vincent
Abstract: Background: Immune modulation by vitamin D3 through dendritic cells (DCs) remains controversial. Human DCs exposed in vitro counteract type‐1 T‐helper (Th1) differentiation and induce regulatory T cells. However, cutaneous application on mice promotes Th2‐driven inflammation resembling atopic dermatitis and relying on thymic stromal lymphopoietin (TSLP) from keratinocytes and T‐cell orientation by TSLP‐stimulated skin DCs. We studied the effects of vitamin D3 in human skin, focusing on TSLP production and the role of skin DCs in T‐cell differentiation. Methods: Human healthy skin explants were exposed in vitro to vitamin D3 analogs. Migrating DCs were analyzed and TSLP quantified in the supernatant. Allogeneic naïve CD4+ T cells were cocultured with DCs to assess their proliferation and cytokine production. Results: Vitamin D3 induced skin DCs to differentiate Th2 cells producing IL‐4 and IL‐13. Vitamin D3 triggered TSLP release in ~30% of skin explants, correlating with IL‐13 detection in Th2 cells. In these donors, blocking TSLP receptor during skin explant cultures abrogated IL‐13 production, yet IL‐4+ Th2 cells were unaffected. Among skin DCs emerged CD14+ cells that had responded directly to vitamin D3 and differed from classical CD14+ dermal emigrants. Vitamin D3‐elicited CD14+ DCs sufficed to promote IL‐4+ Th2 cells in a TSLP‐independent manner. Conclusion: Vitamin D3, despite inducing TSLP in some donors, had a direct influence on skin DCs, affecting their phenotype and ability to drive Th2 responses independently of TSLP. Our findings pave the way toward in vitro systems that accurately model human cutaneous Th2 responses, notably involved in atopic dermatitis. Abstract : Vitamin D3 consistently upregulates CD14 on human skin DCs, yet induces TSLP production in only 30% of skin explants. Skin DCs from TSLP‐producing donors shift naïve T cells into IL‐13+/IL‐4+ Th2 cells. Vitamin D3‐elicited CD14+ DCs from donors that fail to release TSLP are sufficient to generate IL‐4+ Th2 cells. Abbreviations: DC, dendritic cells; LC, Langerhans cell; TSLP, thymic stromal lymphopoietin.